A városi tér használatához kapcsolódó konfliktusok = Conflicts related to the urban space - Boros Lajos (2006)
The aim of this study is to examine the spatial aspects of the extreme social differences and the so-called „beggars regulation” in the cities. In 2005 the city council of Szeged banned the beggars out of the city centre. We applied data from the program called „Szeged Studies”, and, using a questionnaire, we made a focal group survey in one of the poor people’s communities. We found that the population of Szeged sympathized with the poor, however they think that being poor is mainly the personal fault of poor people themselves. Most people think that the city council was right to ban the beggars out of the city centre, and many local citizens think that begging should be forbidden everywhere. Citizens consider the city centre as a place representing the whole city, and thus, it should be clean – from the garbage and from the „unwelcomed persons” as well.